Penerapan Keselamatan Transportasi Air Dan Ketersediaan Alat Pelindung Diri Pada Kapal Motor (Klotok) Penyeberangan Balikpapan Panajam Paser Utara - Maslina, Maslina; pongky, patunru; Zainul, L.M.; ananta, erwin (Program Studi D4 K3 Universitas Balikpapan, 2023)
The method used is to describe systematically, carefully and accurately about the conditions, conditions, motorized sailing ships in the port of Balikpapan Panajam. Identify the availability of safety equipment in accordance with the SOLAS requirements and the Decree of the Director General of Sea Transportation No. PY.66/1/2-2002. An indicator that can be seen from the achievement of the success of this activity is that activity participants are able to know the importance of water transportation safety and the availability of personal protective equipment on motor boats (klotok) properly